Metaflumizone inhibits the honeybee NaV1 channel by targeting recovery from slow inactivation. Issue 23 (12th November 2017) - Gosselin‐Badaroudine, Pascal; Charnet, Pierre; Collet, Claude; Chahine, Mohamed
Abstract : Metaflumizone is the latest addition to the armamentarium of the Na + channel inhibitor insecticide family. We used the Xenopus oocyte expression system and a Markovian model to assess the effect of metaflumizone on Apis mellifera Na + channels (AmNaV 1). Our results reveal that metaflumizone inhibits AmNaV 1 channels by targeting the kinetics of recovery from slow inactivation. Multistate modeling of fast and slow inactivation of the AmNaV 1 channel made it possible to study the effects of metaflumizone on a set of rate constants underlying the transition between the open and inactivated conformations and provided insights into their specificity. We conclude that the methods we used could be extended to assessing the toxicity of other Na + channel inhibitor insecticides. Abstract :